Scala for Java developers : build reactive, scalable applications and integrate Java code with the power of Scala - Alexandre, Thomas (Community experience distilled., 2014)
This step-by-step guide is full of easy-to-follow code taken from real-world examples explaining the migration and integration of Scala in a Java project. If you are a Java developer or a Java architect, working in Java EE-based solutions and want to start using Scala in your daily programming, this book is ideal for you. This book will get you up and running quickly by adopting a pragmatic approach with real-world code samples. No prior knowledge of Scala is required.